The Influence of Casual Mobile Games and Play-to-Earn Games on User Attraction Mediated by the TapTap Application on Android OS and iOS Platforms - Galihwara; Michael Christian; Liem Bambang Sugiyanto; Danial Thaib (International Journal Labs, 2026)
This study analyzes the influence of mobile game types—especially casual and play-to-earn games—on user attractiveness, considering the mediating role of the TapTap application on Android and iOS platforms. A contradictory phenomenon in the mobile gaming industry, where casual games generate high interest and engagement while potentially financially rewarding play-to-earn games tend to attract lower user interest, serves as the background for this study. Marketplaces are used as mediation variables to represent the quality of user experience, including user experience, accessibility, engagement, ease of navigation, and cross-platform application stability. The research employed a quantitative approach with a survey of the gamer community in the Greater Jakarta area through the Indie Game Studio organization, analyzed using descriptive methods and t-statistic-based mediation analysis. The results are expected to make theoretical contributions to the study of consumer behavior and digital business, as well as provide practical implications for developers in designing inclusive mobile games oriented toward user experience. The study has limitations in terms of regional scope and the types of games examined. The research findings provide theoretical implications by highlighting the importance of inclusive user experience and accessibility for gamers with disabilities. From a practical perspective, the results can assist game developers and platform providers in designing marketing strategies and app quality that enhance user engagement.